DETEKSI Mycobacterium tuberculosis DARI KULTUR MGIT BERDASARKAN GEN katG - Prima Nanda Fauziah; Sitti Romlah; Arif Khozinul Asrori (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2020)
Tuberculosis (TB) is a respiratory disease caused by infection of Mycobacterium tuberculosis. Currently, many M. tuberculosis strains have resistant toward to two or more anti-tuberculosis drugs (known as MDR-MTB). One of the gene marker to MDR-MTB is the katG gene. Mutation of katG can be causes the activity of the M. tuberculosis catalase-peroxidase enzyme so that the bacteria become resistant isoniazid (INH) OAT. The aimed of this research was to know the presence of KatG gene in isolate M. tuberculosis from MGIT culture. The sample used was MGIT isolate with 20 samples and then amplified using PCR method. The result showed that there were 4 samples the presence of DNA bands suspected KatG genes ± 317 bp from the MGIT cultured sample. In conclusion, the KatG gene was successfully amplified by PCR method with primer forward and reverse visualization by electroforesis. Sequencing analysis needs to be done on the PCR result in order to see the mutations that occur and to confirm the sample homology with data contained in GenBank on the genes of the KatG, and then to know the presence or absence of mutations in katG genes.